The Effectiveness of The Spelling Method to Upgrade The Writing Skill of Students - Aniatul Khasanah; Agus Nu'man (Al-Kafaah : Journal of Arabic Language and Linguistics Education (ALLE), 2022)
Writing is one of the language skill used in indirect communication, the writing skill is not acquired naturally, but must go through a process of learning and practice. This research is a quantitative research in an experimental design style. The type of research used in this research is a pre-experimental design in the form of a one-group pre-test design. The research data was obtained by conducting a written pre-test and a post-test on the subject “Our School Diaries”. The results of calculating the t-test at a significant level of 0.05 obtained a calculated value of 0.174. Therefore, it can be concluded that the effective use of a dictation method to improve the writing skill of first-grade students from Nour El-Huda Intermediate School for Girls, Flean Kavogan Situbondo.